Quantitative comparison of pre-therapy 99mTc-macroaggregated albumin SPECT/CT and post-therapy PET/MR studies of patients who have received intra-arterial radioembolization therapy with 90Y microspheres. Issue 109 (December 2018) - Knešaurek, Karin; Tuli, Abbas; Pasik, Sara D; Heiba, Sherif; Kostakoglu, Lale
Highlights: PET/MRI post-therapy 90 Y studies are feasible and useful for 90 Y dosimetry calculations. Due to better MRI soft tissue contrast, liver contours are usually better seen in PET/MRI images than in MAA SPECT/CT images. The two main contributors to the difference between 90 Y dosimetry calculations using MAA versus 90 Y PET/MRI can be attributed to the changes in catheter positioning as well as the liver ROIs used for the calculations. 90 Y dosimetry values obtained from pre-therapy MAA SPECT/CT scans and PET/MRI post-therapy 90 Y studies were not significantly different. Abstract: Objective: The aim of our study was to compare yttrium -90 ( 90 Y) dosimetry obtained from pre-therapy 99m Tc-macroaggregated albumin (MAA) SPECT/CT versus post-therapy PET/MRI imaging among patients with primary or metastatic hepatic tumors. Materials and methods: Prior to 90 Y radioembolization (RE), 32 patients underwent a scan using MAA mimicking 90 Y distribution. After RE with 90 Y microspheres, the patients were imaged on a PET/MRI system. Reconstructed images were transferred to a common platform and used to calculate 90 Y dosimetry. The Passing-Bablok regression scatter diagram and the Bland and Altman method were used to analyze the difference between dosimetry values. Results: For MAA and PET/MRI modalities, the mean liver doses for all 32 subjects were 43.0 ± 20.9 Gy and 46.5 ± 22.7 Gy, respectively, with a mean difference of 3.4 ± 6.2 Gy. The repeatibility coefficient was 12.1 (27.0% of the mean). The Spearman rank correlation coefficient was high (ρ = 0.92). Although, there was a substantial difference in the maximum doses to the liver between the modalities, the mean liver doses were relatively close, with a difference of 24.0% or less. Conclusions: The two main contributors to the difference between dosimetry calculations using MAA versus 90 Y PET/MRI can be attributed to the changes in catheter positioning as well as the liver ROIs used for the calculations. In spite of these differences, our results demonstrate that the dosimetry values obtained from pre-therapy MAA SPECT/CT scans and PET/MRI post-therapy 90 Y studies were not significantly different.